CRISPR-Cas9 System: The Latest Genome Editing Technology as A Future Therapy for Oral Diseases - Anis, Rajab; Alhawaris (YARSI Dental Journal, 2024)
Abstract Introduction: CRISPR (Clustered Regularly InterSpacedPalindromic Repeats) is a technology with demonstratedcapability in modifying, repairing, and substituting genecomponents (genome editing). The system relies on Cas9enzyme (CRISPR-associated protein-9 nuclease) and gRNA (guide ribonucleic acid). Various diseases tied to specificgenes in the human genome are linked to oral cavity conditions. Objective: A literature review was used in this study to explain the potential application of CRISPR/Cas9 technology as a therapy for oral diseases in the future.Discussion: The application of CRISPR/Cas9 could lead to the identification of gene impairments and the discovery of genes counteracting tumor-triggering ones responsible for oralcancer. Additionally, it has utility in cases of microorganism infection in the oral cavity, such as targeting the glycosyltransferase encoding gene in Streptococcus mutans.This interference disrupts EPS (extracellular polymericsubstance) matrix synthesis, impeding biofilm formation.Conclusion: CRISPR/Cas9's effectiveness in altering bacterialpopulations or faulty genes presents an opportunity to address intricate oral diseases, potentially revolutionizing dental care. However, despite its promise, clinical trials involving this technology remain at an early stage and are relatively obscure, especially within dentistry. Therefore, a comprehensive body of literature is essential to foster understanding and awarenessof this groundbreaking advancement. Keywords: CRISPR/Cas9, Genome Editing, Oral disease ABSTRAK Latar Belakang: CRISPR (Clustered Regularly InterSpaced Palindromic Repeats) merupakan teknologi yang terbukti mampu memodifikasi, memperbaiki, dan mengganti komponen gen (genome editing). Sistem ini bergantung pada enzim Cas9 (protein-9 nuklease terkait CRISPR) dan gRNA (panduan asam ribonukleat). Berbagai penyakit yang berhubungan dengan gentertentu dalam genom manusia juga berhubungan dengan kondisi mulut. Tujuan: Tinjauan literatur digunakan dalampenelitian ini untuk menjelaskan potensi penerapan teknologiCRISPR/Cas9 sebagai terapi penyakit mulut di masa depan.Pembahasan: Penerapan CRISPR/Cas9 dapat mengarah padaidentifikasi kerusakan gen dan penemuan gen yang melawan gen pemicu tumor yang menyebabkan kanker mulut. Selain itu, memiliki kegunaan dalam kasus infeksi mikroorganisme dirongga mulut, seperti menargetkan gen penyandiglikosiltransferase pada Streptococcus mutans. Gangguan ini mengganggu sintesis matriks EPS (zat polimer ekstraseluler),sehingga menghambat pembentukan biofilm. Kesimpulan:Efektivitas CRISPR/Cas9 dalam mengubah populasi bakteri atau gen yang salah memberikan peluang untuk mengatasi penyakit mulut yang rumit, yang berpotensi merevolusi perawatan gigi. Namun, meskipun menjanjikan, uji klinis yang melibatkan teknologi ini masih berada pada tahap awal dan relatif tidak jelas, terutama dalam bidang kedokteran gigi. Oleh karena itu, kumpulan literatur yang komprehensif sangat penting untuk menumbuhkan pemahaman dan kesadaran akan kemajuan inovatif ini. Kata Kunci: CRISPR/Cas9, Genome Editing, Penyakit Mulut